Recursos multimídia na promoção de habilidades sociais em crianças com dificuldade de aprendizagem - Lopes, Daniele Carolina (2009)
School has an important socialization role and social skills contribute to the socio-emotional and academic development and also behavior problems reduction. To maximize this contribution, universal social skills programs should be tested and disseminated in schools, with effective participation of teachers, main mediators of interpersonal relationships in this environment. For this, it is necessary to investigate a set of practicable procedures, techniques, and resources in the classroom, attractive for both teachers and students. This study examined aspects of a universal program effectiveness, conducted by the teacher, using the audiovisual resources RMHSC-Del-Prette, which has already proved its effectiveness in selective programs conducted by a psychologist. The practicability and effectiveness of the program were evaluated in terms of: (a) impact on social skills, academic competence and behavior problems of all students from two classes, (b) impact on the repertoire of three children from each class with low academic performance, also evaluated on an ongoing basis, (c) integrity of the intervention applied by teachers. Two teachers and their students participated in three classes of fourth grade in a private school. The students evaluation was different for each class, in Class 1 only students with low academic performance (n = 3) were evaluated and in Class 2 (n = 13) and Class 3 (n = 14), all the students were evaluated. All children were assessed before and after the intervention, through the Social Skills Rating System (SSRS-BR) in its three versions. Before the intervention, the teachers were given a brief training course. The intervention program consisted of 11 sessions of 60 minutes each focusing on differents social skills and sequenced in complexity, which were previously evaluated by teachers. The results of SSRS-BR showed an improvement in Responsibility/Cooperation and Academic Competence in the overall assessment of students from two classes according to teachers evaluation; in Kindness and Self-Control and a decrease in Internalizing Behaviors (Class 2) according to parents evaluation. In relation to children with low academic performance, teachers evaluated that most children improved Responsibility / Cooperation and Academic Competence; the parents evaluated that children improved Global social skills Score, Cooperation and also decreased at least a score of Problematic behaviors; in self-assessment the children improved Self-Control. Data from continuous assessment of students with low academic performance indicated that most improved the quality of social skills after the intervention program. The intervention was implemented with integrity of 80% for Teacher 1 (Classes 1 and 3) and 75% for Teacher 2 (Class 2). In summary, the data indicated that the universal social skill program using the RMHSC-Del-Prette produced substantial changes, especially in cooperative behaviors in academic performance and behavior problems (parental assessment) when it was applied by the teacher, including children with low academic performance. It was found that, in implementing this program, the integrity equal to or above 75% was able to produce changes in children's behavior, however, the importance of teacher training and the importance of research about characteristics of the agent's intervention during the implementation of a program is discussed.